Tata Kelola Obat JKN: Peran Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS-K) dalam Belanja Obat Strategis - Yusi Anggriani; Nurita Andayani; Mawaddati Rahmi; Rasta Naya Pratita; Prih Sarnianto; Atmiroseva Atmiroseva; Erfan Chandra Nugraha; Citra Jaya (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
The National Health Insurance System (JKN) has social and equity insurance principles aiming participants receive basic health benefits. This raises must-have other requirements for circulated medicine, namely availability and accessibility. Thus, this must meet the elements of safety, efficacy/ benefits, good quality, market availability, and easy accessibility. However, drug shortages problem still occurs and ranks 3rd for BPJS Kesehatan services complaints. This study is to identify opportunities and constraints of BPJS in strategic health purchasing to increase access to JKN medicine . This is a crosssectional study using quantitative and qualitative methods. Quantitative research uses Structural Equation Modelling (SEM), while qualitative uses Focus Group Discussion (FGD). This found the problem roots related to JKN medicine shortages, including limited human resource capabilities, in optimal planning processes, e-purchasing method constraints, e-purchasing system and manual purchases medicine prices differences, medicines ordering long lead time, and in optimal BPJS Kesehatan role as a strategic health purchaser. Therefore, it is to increase BPJS Kesehatan’s role as an active purchaser by making an information system for all medicine use in JKN services, forming a Drugs Advisory Board/JKN drug working group and coordination between policy-making institutions to optimize BPJS Kesehatan role in ensuring JKN medicines access.